2019
DOI: 10.1002/mp.13688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of tissue deformation during radiofrequency and microwave ablation procedures: Influence of output energy delivery

Abstract: Purpose The purpose of this study was to quantitatively analyze tissue deformation during radiofrequency (RF) and microwave ablation for varying output energy levels. Methods A total of 46 fiducial markers which were classified into outer, middle, and inner lines were positioned into a single plane around an RF or microwave ablation applicator in each ex vivo bovine liver sample (8 cm × 6 cm × 4 cm, n = 18). Radiofrequency (500 kHz; ~35 W average) or microwave (2.4 GHz; 50–100 W output, ~35–70 W delivered) abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 43 publications
(123 reference statements)
0
19
0
Order By: Relevance
“…HR, hazard ratio; CI, confidence intervals; OS, overall survival; DFS, disease-free survival; HBV, hepatitis B virus; HCV, hepatitis C virus; CTP, Child-Turcotte-Pugh; ALBI, albumin-bilirubin; AFP: αfetoprotein; ALB: albumin; TBIL: total bilirubin; AST, aspartate aminotransferase; ALT, alanine aminotransferase; PV, portal vein; HV, hepatic vein; RFA, radiofrequency ablation of residual tumor following RFA, and this could manifest as early LTP during follow-up. While the technical characteristics of RFA and MWA are quite similar, they exhibit several differences in their physical mechanisms of thermogenesis [22][23][24]. The significant difference is that during RFA, heat is confined to zones of high current density, while during MWA, it is generated in a fixed space around the antenna applicator.…”
Section: Discussionmentioning
confidence: 99%
“…HR, hazard ratio; CI, confidence intervals; OS, overall survival; DFS, disease-free survival; HBV, hepatitis B virus; HCV, hepatitis C virus; CTP, Child-Turcotte-Pugh; ALBI, albumin-bilirubin; AFP: αfetoprotein; ALB: albumin; TBIL: total bilirubin; AST, aspartate aminotransferase; ALT, alanine aminotransferase; PV, portal vein; HV, hepatic vein; RFA, radiofrequency ablation of residual tumor following RFA, and this could manifest as early LTP during follow-up. While the technical characteristics of RFA and MWA are quite similar, they exhibit several differences in their physical mechanisms of thermogenesis [22][23][24]. The significant difference is that during RFA, heat is confined to zones of high current density, while during MWA, it is generated in a fixed space around the antenna applicator.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed simulation model showed a good agreement of the temperature and contraction-induced displacement with the experimental in vitro results. More recently, (Liu and Brace, 2019) reported an experimental study on bovine liver to quantitatively analyze the tissue deformation during RFA and MWA. It was reported that the tissue dimensions contracted by 5% post RFA and 20-65% post MWA procedures.…”
Section: Incorporation Of the Mechanical Deformation Modelmentioning
confidence: 99%
“…MWA has some potential advantages over RFA including faster ablations, higher temperature which is not limited by electric impedance, less sensitivity to tissue types with more consistent results, relatively insensitivity to “heat sinks,” and ability to create much larger ablation zones. For lesions larger than 3 cm, particularly those over 5 cm, MWA is significantly better than RFA 18‐22 . Furthermore, multiple MWA antennas can be positioned into target lesions and activated simultaneously, which maximizes nearly spherical ablation zone 23 .…”
Section: Mechanism and Advantages Of Mwamentioning
confidence: 99%
“…For lesions larger than 3 cm, particularly those over 5 cm, MWA is significantly better than RFA. [18][19][20][21][22] Furthermore, multiple MWA antennas can be positioned into target lesions and activated simultaneously, which maximizes nearly spherical ablation zone. 23 Lung ablation zone was reported as large as 54.8 ± 8.5 mm (mean ± SD) in animal studies.…”
mentioning
confidence: 99%